Synthesis of Adsorbent from Bagasse for Methylene Blue Adsorption - Nurhasni Nurhasni; Sariana Harahap; Ahmad Fathoni; Hendrawati Hendrawati (Syarif Hidayatullah State Islamic University, 2021)
The ability of bagasse adsorbents to adsorb methylene blue without activation using 0.5 M H2SO4 solution was examined. Methylene blue is widely used in the textile industry because it produces bright colors, and the dyeing process is fast and easy. This research aims to determine the optimum adsorption conditions, namely the variations in contact time, dye concentration, adsorbent mass, and pH effect on methylene blue, which were carried out using the batch method. Furthermore, the adsorbents were characterized by FT-IR and SEM. The optimum state of the bagasse adsorbent to adsorb methylene blue dye has a mass of 0.5 grams, a contact time of 30 minutes, a concentration of 50 ppm, and a pH of 5. The character of the adsorbent after activation with H2SO4 was better than without activation. The highest adsorption efficiency of methylene blue dye in the batch method was 99.67%. The FTIR spectrum of the bagasse adsorbent showed OH, C-H, C=O, C=C, and C-O functional groups. The adsorption isotherm model for methylene blue dye follows the Langmuir isotherm since the graph obtained is linear with the correlation coefficient (R2) = 1, where the adsorbent has a homogeneous surface.